Tol matol: pyari nazmoo ka intekhab - Sufi, Ghulam Mustafa Tabassum (Feroz sons Karachi, 2009)
A collection of lovely poems. This book introduces children to the beauty of poetry and language. It helps them develop their imagination and appreciation for the written word.